2013
DOI: 10.5888/pcd10.120356
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fruit and Vegetable Consumption Among Low-Income Customers at Farmers Markets: Philly Food Bucks, Philadelphia, Pennsylvania, 2011

Abstract: IntroductionWe evaluated whether Philly Food Bucks, a bonus incentive program at farmers markets, is associated with increased fruit and vegetable consumption and Supplemental Nutrition Assistance Program (SNAP) sales at farmers markets in low-income areas.MethodsA convenience sample of 662 customers at 22 farmers markets in low-income neighborhoods in Philadelphia, Pennsylvania, was surveyed via face-to-face interviews. Questions addressed shopping characteristics, self-reported change in fruit and vegetable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
115
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 11 publications
(16 reference statements)
9
115
0
Order By: Relevance
“…However, these associations may also be a result of a healthier eating identity among those who shop at farmers markets (36) compared with those who do not shop at farmers' markets. Previously mentioned, Young et al (22) suggest that when incentive programmes are provided at farmers' markets in low-income areas, providing greater financial access to markets, participants report eating more FV than nonparticipants. However, in the current study, neither objectively measured nor perceived access (distance) to farmers' markets was associated with farmers' market use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these associations may also be a result of a healthier eating identity among those who shop at farmers markets (36) compared with those who do not shop at farmers' markets. Previously mentioned, Young et al (22) suggest that when incentive programmes are provided at farmers' markets in low-income areas, providing greater financial access to markets, participants report eating more FV than nonparticipants. However, in the current study, neither objectively measured nor perceived access (distance) to farmers' markets was associated with farmers' market use.…”
Section: Discussionmentioning
confidence: 99%
“…'Double Bucks' and similar interventions, whereby low-income individuals' SNAP benefits are multiplied when used at local farmers' markets, have shown promise. In Philadelphia, Young et al found that when SNAP participants were given incentives to spend $US 5 of SNAP benefits at a local farmers' market, SNAP transactions increased and participants reported consuming more FV (22) . In New York City, 'Health Bucks' resulted in greater SNAP benefit redemption in markets (23) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Private charities have long provided services like food pantries, food banks, and soup kitchens. Prior to the 1980s these programs were small in scale and scope, but the recession of the 1980s, coupled with a steep decline in social spending, led to a dramatic expansion of private charities [12]. During the recent Great Recession, private charities similarly played an important role in aiding households suffering from food insecurity [22,23].…”
Section: The History and Importance Of Public And Charitable Assistanmentioning
confidence: 99%
“…For instance, Jones and Bhatia discuss the introduction of EBT terminals in farmers' markets, and the subsequent increase in money spent at farmers' markets [11]. Other research has examined the role that bonus buck programs have played in improving Supplemental Nutrition Assistance Program (SNAP, formerly known as food stamps) sales at farmers' markets in low income areas [12]. Still other research has examined the effectiveness of different ways of accepting food assistance programs.…”
Section: Introductionmentioning
confidence: 99%